usborne peep inside : how a helicopter works - Bryan, Lara; Medeiros, Giovana (London : Usborne Publishing Ltd., 2022)
This book of first words is all about YOU. There are lots of things to name and spot-and plenty of little holes to look through.
Keywords: Helicopters -- fiction